The relationship between p53 mutations and differential sensitivity to anti-cancer drugs in oesophageal cancer cell lines - Johnson, Melanie (Division of Medical Biochemistry, 2024)
In South Africa, cancer of the oesophagus is the leading cause of death in black males and overall the fourth most common cancer. Development of resistance to chemotherapeutic agents hinders the successful treatment of several cancers. In order to characterise drug resistance in several South African oesophageal cancer cell lines, sensitivity to anti-cancer drugs, presence of P-glycoprotein (P-gp) and glutathione-S-transferase (GST), and p53 mutations were investigated. Chemosensitivity of the WHCO1, WHC03 and HCu-13 cell lines to 7 anti-cancer agents was determined. WHC03 was relatively resistant to cisplatin and transplatin, but sensitive to vinblastine, vincristine, 5-fluorouracil and 5-fluorouridine. HCu-13 was sensitive to cisplatin and transplatin, but resistant to the other drugs. WHCO1 was of intermediate sensitivity, while all the cell lines were senstitive to doxorubicin. Overexpression of P-gp, a cell membrane-bound drug efflux pump, results in resistance to several unrelated hydrophobic drugs, of which doxorubicin is one. NIH-3T3-MDR, a P-gp transfected fibroblast cell line, exhibited a doxorubicin IC50 (concentration of drug resulting in 50% cell viability) greater than 5-fold that of WHCO1, WHC03 and HCu-13. Using FACS and a P-gp monoclonal antibody (4E3), P-gp was detected in NIH-3T3-MDR but not in the oesophageal cancer cell lines, consistent with previous reports of oesophageal tissue being P-gp negative and supporting their doxorubicin susceptibility profiles. It has been reported that certain p53 mutants trans-activate the multidrug resistance gene, MDRJ, which encodes P-gp. Single stranded conformation polymorphism analysis and direct sequencing of exons 5, 6 and 7 ofp53 revealed a unique ACC deletion in exon 7 of WHC03 and a G to T point mutation in exon 5 of HCu-13. Since P-gp was not detected in WHC03 nor HCu-13, these mutations are unlikely to be involved in activation of the MDRJ promoter in these cell lines in vitro, but may play a role in conferring differential drug sensivity. An elevated level of GST activity has been implicated in cellular resistance to alkylating drugs and cisplatin, which has a similar mechanism of action. WHC03 was found to be greater than 11 fold more resistant to cisplatin than WHCO1 and HCu-13. However, GST activity ofWHC03 and HCu-13 was similar, and 1 .5 times that of WHCO1, thus implying no correlation between GST activity and cisplatin susceptibility in these cell lines. Furthermore, selection of WHCO1 for resistance to cisplatin to 40µg/ml, over 4 weeks, resulted in a greater than 100-fold increase in resistance, without a corresponding increase in GST activity. The presence of p53 mutations in WHC03 and HCu-13, which also had the greatest GST activity, suggests a role for p53 in the expression of GST, and warrants futher investigation. Differential drug sensitivity, intrinsic resistance and rapidly acquired resistance to cisplatin may have implications in the chemotherapy of oesophageal cancer and call for individualised therapy protocols.